Neointimal erosion resulting in very-late stent thrombosis. Issue 4 (June 2019) - Mori, Hiroyoshi; Sone, Hiromoto; Takei, Yosuke; Tashiro, Kazuma; Sasai, Masahiro; Maeda, Atsuo; Sato, Tokutada; Suzuki, Hiroshi
Abstract : Supplemental Digital Content is available in the text.